Survival Rates for Porcelain Laminate Veneers: A Systematic Review - AlJazairy, Yousra H. (European Journal of Dentistry, 2020)
The aim of this systematic review was to analyze and compare the most up-to-date information available on long-term, medium-term, and short-term survival rates of porcelain laminate veneers (PLVs) and investigate the homogeneity in current studies or lack of it. An electronic search was performed using PubMed, Ovid MEDLINE, Cochrane Library, Web of Science, EBSCO, Science Direct, Wiley, and Scopus databases. Based on the PRISMA guidelines, the main inclusion criteria consisted of research articles published after the year 2000, in vivo studies with a follow-up period of at least 1 year and reporting of the Kaplan–Meier estimated cumulative survival rates. Quality assessment of the included studies was performed using the modified systematic assessment list consisting of 24 items. Thirty full-text articles were reviewed in detail. A total of 30 articles met the inclusion criteria and were selected for qualitative synthesis. The remaining 27 publications were retained to discuss the heterogeneity in the current literature and reported longevity of veneer restorations. A conclusive estimation of the longevity of PLVS beyond 20 years is lacking. The availability of evidence in the current literature is limited in terms of sample size and duration of follow-up. However, the majority of studies have concluded that PLVs have high-success rates and predictable patient outcomes. The present literature indicates an increased heterogeneity among research study designs. Researchers should aim for homogeneous study designs that can be included in systematic reviews and meta-analyses.
Keywords: porcelain laminate veneers; longevity; follow-up; failure; ceramic; restorations; homogeneity